PENGEMBANGAN BAHAN AJAR MENULIS PUISI BERBASIS DEEP LEARNING UNTUK SISWA KELAS VIII MTs SALAFIYAH CUNGKUP - Jazilatul Khoiro; Anisa Ulfah; Nisaul Barokati Selirowangi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning to write poetry still faces obstacles due to limited teaching materials that do not guide students in a gradual and meaningful manner. This study aims to develop Deep Learning-based poetry writing teaching materials, determine the level of feasibility, and test their effectiveness on eighth-grade students at MTs Salafiyah Cungkup. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and pretest and posttest tests. The results showed that the teaching materials obtained a validation percentage of material experts of 96% and media experts of 95% with a very feasible category. Student responses showed a very practical category. The effectiveness of the teaching materials was shown by an increase in the average score of students from 62.5 in the pretest to 95.5 in the posttest with an N-Gain value of 0.88 (high category). Thus, Deep Learning-based poetry writing teaching materials were declared feasible, practical, and effective for use in learning.